ORDER FIKTIF TERHADAP DRIVER GOJEK DAN UPAYA PERLINDUNGANNYA - Inka Renandani; Adi Suliantoro (Fakultas Hukum Universitas Stikubank, 2020)
Transportation is a very important aspect of its existence in society, both the transportation of people and goods. One of the well-known online transportation companies in Indonesia is PT Gojek Indonesia. During its development, there have been actions committed by unscrupulous people in the community that harm online motorcycle taxi drivers, namely fictitious / fake orders. Fictitious Order is an order that starts with creating a fake account through an online transportation application that can harm the company.The problem is what is the form of the agreement between the driver and the user and is there the responsibility of PT Gojek Indonesia. The method used in this research is sociological juridical, with data sources in the form of interviews. The results of the analysis were presented descriptively and analytically.The results show that there is no legal regulation that regulates protection for Gojek drivers who experience fictional orders. But from the PT. Gojek provides compensation in the form of compensation money. However, this is not widely used by drivers, because the process of disbursing compensation money takes time, so the driver as the victim prefers to bring the results of the fictitious order himself or sell it to someone else. Keywords: Protection, Transportation, Gojek